2020
DOI: 10.1177/8755293019899965
|View full text |Cite
|
Sign up to set email alerts
|

Design strategies to achieve target collapse risks for reinforced concrete wall buildings in sedimentary basins

Abstract: Studies of recorded ground motions and simulations have shown that deep sedimentary basins can greatly increase the damage expected during earthquakes. Unlike past earthquake design provisions, future ones are likely to consider basin effects, but the consequences of accounting for these effects are uncertain. This article quantifies the impacts of basin amplification on the collapse risk of 4- to 24-story reinforced concrete wall building archetypes in the uncoupled direction. These buildings were designed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…As a result, the spectral accelerations from the 2014 to the 2018 NSHM Uniform Hazard Spectrum (UHS) for a hazard level with a 2% probability of exceedance in 50‐year is approximately 50% larger for periods in the range of 1–4 s. Increases in spectral acceleration due to basin amplification are larger at longer periods. For instance, the increase in spectral acceleration at a period of 0.2 s is only 15%, whereas for a 2.0 s period, the increase is 66% 12 . Increases in spectral acceleration from the 2014 NSHM to the 2018 NSHM are negligible for out‐of‐basin sites within Western Washington State.…”
Section: Considering Deep Sedimentary Basins In Structural Designmentioning
confidence: 96%
See 4 more Smart Citations
“…As a result, the spectral accelerations from the 2014 to the 2018 NSHM Uniform Hazard Spectrum (UHS) for a hazard level with a 2% probability of exceedance in 50‐year is approximately 50% larger for periods in the range of 1–4 s. Increases in spectral acceleration due to basin amplification are larger at longer periods. For instance, the increase in spectral acceleration at a period of 0.2 s is only 15%, whereas for a 2.0 s period, the increase is 66% 12 . Increases in spectral acceleration from the 2014 NSHM to the 2018 NSHM are negligible for out‐of‐basin sites within Western Washington State.…”
Section: Considering Deep Sedimentary Basins In Structural Designmentioning
confidence: 96%
“…37 The resulting synthetics highlight the considerable amplification of spectral accelerations, ranging from factors of 2 to 5, for periods of 1 to 10 s, for sites within the Seattle basin. Marafi et al 12 showed that inside the basin the spectral accelerations of the simulated M9 CSZ ground motions at periods of 1.5 to 4 s were greater than the spectral accelerations of the ASCE 7-16 risk-targeted maximum considered earthquake (MCE R ), which has a return period of around 2000 years in Seattle. Table 2 summarizes the CMS spectral acceleration, at the fundamental period of each REF archetype, using the 2014 and 2018 NSHMs for intensity levels with return periods of 975 and 2475 years.…”
Section: Seismic Hazard and Ground Motionsmentioning
confidence: 99%
See 3 more Smart Citations